Comparative determination of ventilatory efficiency from constant load and incremental exercise testing - Algul, S.; Ugur, F. A.; Ayar, A.; Ozcelik, O. (Cellular and Molecular Biology, 2017)
The analysis of the relationships between minute ventilation (VE) to CO2 output (VCO2), referred to as ventilatory efficiency, in response to incremental exercise testing, is considered a useful index for assessing the presence and severity of cardiopulmonary and metabolic diseases. The effects of constant load exercise testing performed at work intensity associated with anaerobic threshold (AT) and respiratory compensation points (RCP), on the accurate measurements of ventilatory efficiency are not well known. The aim of this present study was to investigate the reliability of the VE/VCO2 ratio obtained from constant load exercise tests performed with two important metabolic rates (at the AT and RCP) and compare it to that of those of incremental exercise tests. A total of 20 young male (20.8±0.4 yr) subjects initially performed an incremental exercise test and then two constant load exercise tests, on different days. Respiratory and pulmonary gas exchange variables were used to estimate AT and RCP. A paired t-test was used to analyse data. AT and RCP (average) occurred the at 60% and at 71% of peak O2 uptake, respectively. The lowest VE/VCO2 ratio recorded within the first 2 minutes of constant load exercise tests with a work load of AT (26.4±0.3) and RCP (26.7±0.5) was not statistically different from the lowest ratio obtained from the incremental exercise tests (26.0±0.7). In the constant load exercise test, despite the different metabolic rates, the increase in ventilation corresponded closely with the increase in CO2 production, reflecting an optimal ventilation and perfusion ratio. Clinicians should consider the constant load exercise test work load associated with AT and RCP as it provides a meaningful lowest value for ventilatory efficiency.